Dense + Green : Innovative Building Types for Sustainable Urban Architecture - Schröpfer, Thomas (Birkhäuser, 2015)
The integration of nature in architecture is a key concern of sustainability. Dense + Green explores new architectural typologies that emerge from the integration of green components such as sky terraces, vertical parks and green facades, in high-density buildings. In-depth case studies on the most relevant building types are complemented by expert essays that demonstrate the current paradigm shift in the sustainable urban environment.